Characteristics and Dynamics of Cyberstalking Victimization Among Juveniles and Young Adults - Walsh, Wendy A. (Violence against women, 2025)
Using the nationally representative Ipsos online KnowledgePanel, the sample included three hundred thirty-six 18- to 28-year-olds who retrospectively reported first cyberstalking incidents as juveniles (9- to 17-year-olds) or adults. Half of the sample first experienced cyberstalking as juveniles and half first experienced it as adults. Juveniles were more likely to have more than two perpetrators in the same episode, to experience more violent threats, and to avoid people because of what happened. Few reported the incident to the police, with juveniles less likely to report it to the police. Cyberstalking of juveniles appears just as or more serious than cyberstalking of adults.